Effects of Fire Frequency on Seed Sources and Regeneration in Southeastern Amazonia - Cury, Roberta Thays dos Santos; Montibeller-Santos, Cinthia; Balch, Jennifer K.; Brando, Paulo Monteiro; Torezan, José Marcelo D. (Frontiers in Forests and Global Change, 2020)
The trajectory and recovery time of fire-disturbed forests depend on the capacity of seedlings and resprouts to get established over time. Here, we investigated the mechanisms associated with fire effects on postfire regeneration in the context of a large-scale fire experiment located in southeastern Amazonia. Specifically, we tested the hypothesis that recurrent understory fires reduce forest regeneration capacity by reducing the recruitment of seedlings, the viability of the soil seed bank, the seed rain, and the resprouts. The experiment was comprised of three 50-ha plots: an unburned control, and two plots that were experimentally burned three (triennially) or six (annually) times between 2004 and 2010. Seedlings represented 2.4% and 0.6% of the seed rain and soil seed bank in the Control and burned treatment plots, respectively. Compared to the control, the triennial burns caused more reduction than the annual ones in seed rain (-42% versus -10%) and seed bank (-78% versus -50%). These fire-related reduction in seed rain in both treatments explain most of the low postfire density of seedlings (0.4 and 0.8 ind/m2, respectively), compared with the Control (2,9 ind/m2). The three-year interval between fires contributed to highest mortality of seeds stored in the soil than in the annual burn treatment, where fires were less severe. However, there were 5.5 times more resprouting in the plot burned triennially compared with the one burned annually. In both treatments, though, the number of resprouts declined over time. In conclusion, seeds from both seed rain and seed bank and resprouting were negatively affected by both fire frequencies, reducing the likelihood of native species recovery by altering the regeneration pathways. This situation is expected to be increasingly common in southeastern Amazon forests, particularly under warmer and dryer climate conditions.